Numerical Research on Convective Heat Transfer and Resistance Characteristics of Turbulent Duct Flow Containing Nanorod-Based Nanofluids - Fangyang Yuan; Jianzhong Lin; Jianfeng Yu (Journal of Nanotechnology)
A coupled numerical model for nanorod-based suspension flow is constructed, and the convective heat transfer and resistance characteristics of the nanofluid duct flow are investigated. The numerical results are verified by experimental results and theoretical models. Most of nanorods are located randomly in the bulk fluid, while particles near the wall aligned with the flow direction. Friction factor of nanofluids with nanorods increases with higher particle volume concentration or aspect ratio, but the increment reduces when the Reynolds number gets larger. The relative Nusselt number is obtained to characterize the intensity of convective heat transfer. The results show that the Nusselt number of nanofluids increases when the particle volume concentration or aspect ratio becomes larger. Compared to increasing the aspect ratio of nanorods, increasing the particle volume concentration would be more effective on enhancing the convective heat transfer intensity in industrial applications although it will cause a slight increase of resistance.